Electroacupuncture Ameliorates Cognitive Impairment by Inhibiting the JNK Signaling Pathway in a Mouse Model of Alzheimer’s Disease - Tang, Yinshan; Xu, Anping; Shao, Shujun; Zhou, You; Xiong, Bing; Li, Zhigang (Frontiers in Aging Neuroscience, 2020)
Electroacupuncture (EA) has become popular for its adjustable strength and frequency and easy quantification in the clinic and has demonstrated therapeutic potential for Alzheimer's disease (AD). However, the mechanism remains unknown. Abnormally activated c-Jun N-terminal kinase (JNK) has been closely related to the pathological process of AD. The aim of this study was to investigate the effect of EA on cognitive impairment and the role of the JNK signalling pathway in AD model amyloid precursor protein (APP)/ presenilin 1 (PS1) mice. The memory and learning ability of each group was assessed using the Morris Water Maze (MWM). Immunofluorescence, immunohistochemistry and Western blot were performed to measure the expression of APP, phosphorylated (P-)JNK, mitogen-activated protein kinase 4 (MKK4), MKK7, c-Jun and caspase-3 in hippocampal tissue samples in APP/PS1 mice after EA intervention. Obvious cognitive deficits were observed in the AD model APP/PS1 mice in the MWM test and were associated with JNK signalling pathway activation and APP upregulation. Four weeks of EA significantly ameliorated the cognitive impairments and inhibited JNK signalling pathway activation and APP upregulation. Taken together, the findings demonstrated that EA can reverse cognitive deficits and substantially lower the burden of APP in AD model APP/PS1 mice, at least partially through inhibiting the JNK signalling pathway and regulating apoptosis signals. Therefore, EA may offer an effective alternative therapeutic approach for AD.